8x - 5 + 3x = 9x + 10
Soluções para a tarefa
Respondido por
1
Resposta:
8x + 3x - 9x = 10 +5
11x - 9x = 15
2x = 15
x = 15/2
x = 7,5
Respondido por
1
Olá, colega!
x = ![\frac{15}{2} \frac{15}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B15%7D%7B2%7D)
Separando os termos invertendo seus sinais, teremos:
8x - 5 + 3x = 9x + 10
8x + 3x - 9x = + 10 + 5
8x + 3x - 9x = + 10 + 5
2x = 15
x = 15/2 = (7,5)
x =
Espero ter ajudado, bons estudos!
Perguntas interessantes
Filosofia,
6 meses atrás
Geografia,
6 meses atrás
Geografia,
6 meses atrás
Sociologia,
6 meses atrás
Matemática,
6 meses atrás
Física,
1 ano atrás
Física,
1 ano atrás
Português,
1 ano atrás